STRATEGI MANAJEMEN PEMBELAJARAN MELALUI PENERAPAN METODE C3T UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR NEGERI 007 LIMBUR MERANGIN - Sumiyati Sumiyati; Sri Yulia Sari; Paujan Azim (STKIP Pesisir Selatan, 2026)
This study aims to determine the application of the C3T method (Smart, Careful, Fast, and Precise) in improving student learning activity in Natural and Social Sciences (IPAS) subjects in grade V of SDN 007 Limbur Merangin. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, namely cycle I and cycle II. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects were 18 grade V students. Data collection techniques were carried out through observation and student learning activity questionnaires, while data analysis was carried out descriptively quantitatively. The results of the study showed that the application of the C3T method can significantly improve student learning activity. In the pre-cycle stage, the percentage of student learning activity was 39,89% with a poor category. After the implementation of the C3T method in the first cycle, it increased to 68,82%, categorized as good, and in the second cycle, it increased again to 89,65%, categorized as very good. Thus, the C3T method has proven effective in increasing student learning activity in science lessons and is able to create a more active, competitive, and enjoyable learning atmosphere.